Users' experiences with e-voting: a comparative case study. (21st December 2009) - Oostveen, Anne-Marie; Van den Besselaar, Peter
A system for electronic voting (e-voting) was developed and tested in 14 field studies. This enabled us to investigate the actual experiences of users when deploying this type of e-governance technology. Are users satisfied with e-voting technology and its usability? Do social groups have different opinions and use of the technology? Does this relate to a digital divide? Will e-voting technology result in increasing voter turnout? We identified serious risks of adoption of e-voting systems for the democratic process, and the assumption that e-voting will increase overall voter turnout is not supported by our research.